1998
DOI: 10.1590/s0037-86821998000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a booster-dose of rabies vaccine on the duration of virus neutralizing antibody titers in bovines

Abstract: Efeito de uma dose de reforço da vacina anti-rábica sobre a duração de títulos de anticorpos neutralizantes do vírus, em bovinos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
4
8
0
3
Order By: Relevance
“…However, single doses of rabies vaccines have been associated with low levels of neutralizing antibodies and also with occurrence of disease in vaccinated animals (9,15). On the other hand, the use of a booster has significantly increased antibody specific levels (2,6,10,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, single doses of rabies vaccines have been associated with low levels of neutralizing antibodies and also with occurrence of disease in vaccinated animals (9,15). On the other hand, the use of a booster has significantly increased antibody specific levels (2,6,10,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…To be considered immune, an individual requires antibody titers ≥ 0.5 IU ml -1 (international units per milliliter) (WHO, 1992) and a number of studies have suggested that this dose should also be applied as the minimum for protection in cattle (SIHVONEN et al, 1994;ALBAS et al, 1998;RODRIGUES DA SILVA et al, 2000;ALBAS et al, 2005). Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, factors such as the quality of the vaccine, the physiological state of the animals and the individual capacity of the immune system response can all contribute to a reduction in the efficiency and effectiveness of vaccination in cattle herds. It should be highlighted that despite the variation in bovine responses, the vaccines used were all properly released, registered and approved by the Ministry of Agriculture, Livestock and Food Supply (ALBAS et al, 1998;GIOMETTI et al, 2006;MARIA et al, 2009). …”
Section: Frequency Of Cattle With Titers Of Antirabies Antibodiesmentioning
confidence: 99%
“…Primeiramente notou-se que a resposta imune humoral anti-rábica nos bovinos dos grupos GC e GP foi heterogênea, ficando confirmada pelo elevado coeficiente de variação (C.V.) dos títulos de anticorpos, para grupos (C.V.= 137,19%) e dias de observação (C.V.= 57,48%), apresentando animais que não responderam à vacinação (títulos de anticorpos <0,50 UI/mL) intercalados com outros que apresentaram títulos de anticorpos protetores mínimos (≥0,50 UI/mL) a elevados. Este fato também foi observado por Ciuchini et al (1981), Albas et al (1998Albas et al ( , 2005, Giometti et al (2006) e Maria et al (2007) avaliando a resposta imune humoral a outras vacinas anti-rábicas. Portanto, esta variação nos títulos de anticorpos nos bezerros pode ser uma característica fisiológica da resposta imune humoral anti-rábica em bovinos primovacinados.…”
Section: Resultsunclassified
“…Além disso, foi observada uma elevada porcentagem de bovinos (75,6%) protegidos. Esta redução nos títulos de anticorpos anti-rábicos é um efeito fisiológico da resposta imune humoral em bovinos primovacinados contra a raiva, pois este fato também foi observado por Albas et al (1998Albas et al ( , 2005, Giometti et al (2006) Apesar da vacina avaliada neste experimento ter excelente capacidade de induzir a soroconversão e de manter os títulos de anticorpos anti-rábicos considerados protetores nos bovinos primovacinados contra a raiva por longos períodos, estes resultados não dispensam a necessidade da aplicação da dose de reforço em bovinos primovacinados conforme preconizado pelo Programa de Controle da Raiva em Herbívoros do Instituto Pasteur.…”
Section: Resultsunclassified